Automatic Optimization System of Cutting Condition for Different Types of Machining Processes - Kadhum, Ali H.; Hatem, Huda (Al-Khwarizmi Engineering Journal, 2009)
This research aims at calculating the optimum cutting condition for various types of machining methods, assisted by computers, (the computer program in this research is designed to solve linear programs; the program is written in v. basic language). The program obtains the results automatically, this occur through entering the preliminary information about the work piece and the operating condition, the program makes the calculation actually by solving a group of experimental relations, depending on the type of machining method (turning, milling, drilling). The program was transferred to package and group of windows to facilitate the use; it will automatically print the initial input and optimal solution, and thus reduce the effort and time required for the calculations, that helps to find the optimum values for the cutting system. Optimum values improved mechanical properties (wear, fatigue, strength …) and gave better productivity.